MISI YANG HOLISTIK KEPADA ORANG YANG BERBEDA KEYAKINAN DI TENGAH MASYARAKAT YANG PLURALIS - Dapot Damanik; Irene; Gracesia Amelia; Nuraini Lumbantobing; Pandapotan Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article explores the concept of holistic mission for individuals of different faiths within the context of a pluralistic society. The main emphasis is on the importance of an inclusive and loving approach. In an increasingly connected and diverse world, the challenges faced by Christian mission are not limited to evangelism alone, but also include efforts to build relationships based on mutual respect and understanding. Holistic mission involves spiritual, social, cultural, and emotional dimensions, enabling dialogue and collaboration among various religions. This article explains the meaning of holistic mission, the significance of interreligious dialogue, appreciation of differences, and the application of the principle of love within the context of mission. By referring to relevant missiological theories and real-life practices, this article aims to provide practical guidance for mission practitioners in navigating complex social dynamics. Through an approach centered on love and understanding, it is hoped that Christian mission can contribute to the creation of a harmonious and inclusive society, where everyone feels valued and accepted, regardless of their religious background.